2013
DOI: 10.1063/1.4824825
|View full text |Cite
|
Sign up to set email alerts
|

Shock compression of aluminum single crystals to 70 GPa: Role of crystalline anisotropy

Abstract: Articles you may be interested inHigh pressure equation of state and ideal compressive and tensile strength of MgO single crystal: Ab-initio calculations J. Appl. Phys. 113, 233504 (2013); 10.1063/1.4811232 Effect of temperature, strain, and strain rate on the flow stress of aluminum under shock-wave compression J. Appl. Phys. 112, 073504 (2012); 10.1063/1.4755792 Effect of compositional variation on the shock wave response of bulk amorphous alloys Yield properties, phase transition, and equation of state of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…Plate-impact experiments were carried out using a two-stage light-gas gun with a 1 ′′ (up to 5.2 km/s) or 0.5 ′′ (up to 7.1 km/s projectile velocity) diameter barrel at the Institute for Shock Physics, Washington State University (Choudhuri & Gupta, 2013). Although the water content of the samples was not measured, Corning fused silica is reported by the manufacturer to have 800-1,000 ppm OH.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plate-impact experiments were carried out using a two-stage light-gas gun with a 1 ′′ (up to 5.2 km/s) or 0.5 ′′ (up to 7.1 km/s projectile velocity) diameter barrel at the Institute for Shock Physics, Washington State University (Choudhuri & Gupta, 2013). Although the water content of the samples was not measured, Corning fused silica is reported by the manufacturer to have 800-1,000 ppm OH.…”
Section: Methodsmentioning
confidence: 99%
“…Although the water content of the samples was not measured, Corning fused silica is reported by the manufacturer to have 800-1,000 ppm OH. Plate-impact experiments were carried out using a two-stage light-gas gun with a 1 ′′ (up to 5.2 km/s) or 0.5 ′′ (up to 7.1 km/s projectile velocity) diameter barrel at the Institute for Shock Physics, Washington State University (Choudhuri & Gupta, 2013). Projectile velocities were measured by a four-beam optical beam-block system with uncertainties of <0.5%.…”
Section: Methodsmentioning
confidence: 99%
“…These studies demonstrated that the mechanical properties of HEAs are highly tunable over a wide range by suitable thermomechanical treatment . Deformation of HEAs at medium to high strain rates (in the range of 10 −2 –10 3 s −1 ) using Split‐Hopkinson Pressure Bar (SHPB) indicated that the mechanism, flow stress, and strain‐hardening were significantly dependent on the strain rate . For some HEAs, a transition in deformation mechanism from dislocation slip to a mixed mode of dislocation‐slip and deformation twinning was observed by increasing strain rate from 10 −3 to 10 2 s −1 .…”
Section: Introductionmentioning
confidence: 95%
“…[14][15][16][17] Deformation of HEAs at medium to high strain rates (in the range of 10 À2 -10 3 s À1 ) using Split-Hopkinson Pressure Bar (SHPB) [2,[18][19][20][21][22] indicated that the mechanism, flow stress, and strain-hardening were significantly dependent on the strain rate. [23][24][25][26][27][28][29][30] For some HEAs, a transition in deformation mechanism from dislocation slip to a mixed mode of dislocation-slip and deformation twinning was observed by increasing strain rate from 10 À3 to 10 2 s À1 . [22,[31][32][33] Several of these HEAs also show inhomogeneous deformation in the form of serrated flow with increasing applied stress.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to accessing extreme thermodynamic states, shock-wave experiments are ideally suited to examine condensed-matter changes in real time (picosecondnanosecond timescales). Although the majority of past studies have involved continuum measurements (e.g., impedance matching and wave profiles) [1][2][3][4]7,8], recent experimental advances are providing real-time microscopic information through in situ, x-ray diffraction (XRD) measurements, including new insights into phenomena such as shock-induced structural transformations [9][10][11] and deformation twinning [12,13].…”
Section: Introductionmentioning
confidence: 99%